2016
DOI: 10.1111/mve.12218
|View full text |Cite
|
Sign up to set email alerts
|

Identification of semiochemicals attractive toSimulium vittatum(IS‐7)

Abstract: Many blackfly species (Diptera: Simuliidae) are economically important insect pests, both as nuisance biters and as vectors of pathogens of medical and veterinary relevance. Among the important blackfly pest species in North America is Simulium vittatum Zetterstedt sensu lato. The objective of this study was to identify compounds excreted by mammalian hosts that are attractive to host-seeking S. vittatum females. The attractiveness of putative compounds to colonized S. vittatum was tested through electrophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Naphthalene has been reported to occur in humans, 22 cattle, 23 and dogs, 24 and it could be involved in location of hosts for blood meals. Our results also support earlier laboratory observations by Verocai et al 25 that naphthalene was attractive to the North American black fly species Simulium vittatum in electroantennogram (EAG) and Y-tube assays. Both S. damnosum s.s. and S. vittatum are zoophilic species that may attack a variety of hosts.…”
Section: Discussionsupporting
confidence: 92%
“…Naphthalene has been reported to occur in humans, 22 cattle, 23 and dogs, 24 and it could be involved in location of hosts for blood meals. Our results also support earlier laboratory observations by Verocai et al 25 that naphthalene was attractive to the North American black fly species Simulium vittatum in electroantennogram (EAG) and Y-tube assays. Both S. damnosum s.s. and S. vittatum are zoophilic species that may attack a variety of hosts.…”
Section: Discussionsupporting
confidence: 92%
“…This loss of efficiency makes mopHLCs less practical for disease monitoring than sHLCs, it may, however, be possible to improve the efficiency of mopHLCs. While there is relatively little data on how anthropophilic simuliids are lured to human hosts, it is clear that skin odour volatiles play a crucial role in luring host-seeking anthropophilic mosquito species [2729]. It could be, thus, that the loss of efficiency of mopHLC-only trapping, which we observed in our experiments, is explained by skin-applied mineral oil preventing or reducing the release of simuliid-attracting skin odour volatiles that are released in sHLCs.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a study using EAG and Y-tube assays identified five compounds: octenol, 2-heptanone, acetophenone, 1-octanol and naphthalene, as attractive to Simulium vittatum Zetterstedt s.l. (Verocai et al 2016). This simulid species is a vector of vesicular stomatitis virus to several livestock species (Cupp et al 1992;Mead et al 2004).…”
Section: Black Flies (Diptera: Simuliidae)mentioning
confidence: 99%